Analisis Sistem Iconnet Terhadap Kinerja PT PLN Icon Plus (Cabang Mamuju) Dalam Penyediaan Layanan Internet Rumah - Salsabila; Nengsih, Yulia; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
This study analyzes the effect of Iconnet system quality on service delivery performance at PT PLN Icon Plus, Mamuju Representative Office. The research adopts a quantitative approach with a causal associative design. Data were collected through questionnaires distributed to 30 respondents who are active Iconnet customers in the Mamuju area and have subscribed for at least six months. Data analysis was conducted using instrument quality testing, classical assumption tests, and simple linear regression analysis. The results indicate that Iconnet system quality has a positive and significant effect on service delivery performance, as evidenced by a significance value of 0.01 (< 0.05). The coefficient of determination shows that system quality contributes 86.9% to the variation in service performance, while the remaining percentage is influenced by other factors outside the research model. These findings confirm that the reliability of technical infrastructure—such as connection stability, bandwidth suitability, and the reliability of the fault reporting system—is a key determinant of operational success and customer satisfaction. The results of this study are expected to serve as an evaluation reference for PT PLN Icon Plus in improving system quality and service performance, as well as a reference for future research related to system quality and service performance in internet service providers.